2014
DOI: 10.1530/erc-14-0229
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes and thyroid cancer: more to it than meets the eye?

Abstract: Immune responses by innate and adaptive immune cells are crucial for the suppression of carcinogenesis and tumor spread. Effector T cells such as, cytotoxic CD8C T (CTL), natural killer (NK), and NK T cells (NKT cells) prevent tumor growth by their ability to induce apoptosis in cancer cells. To circumvent anti-tumor immunity, tumors commonly attract regulatory T cells (Treg), which suppress the function of CTL and NKT cells in a contact-and cytokine-dependent manner. Recent findings in patients with thyroid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The association between PTC and HT was first described in 1955 by Dailey et al [ 5 , 6 ], and the concept of chronic inflammation as a risk factor for the development of malignancies has been well established [ 7 , 8 ]. However, the effect of AITD on PTC remains controversial [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between PTC and HT was first described in 1955 by Dailey et al [ 5 , 6 ], and the concept of chronic inflammation as a risk factor for the development of malignancies has been well established [ 7 , 8 ]. However, the effect of AITD on PTC remains controversial [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor immune microenvironment regulates responses of immune cells and play a critical role in the suppression of cancer development and cancer spread [ 18 ]. Due to their ability to destroy cancer cells, cytotoxic CD8 positive T-lymphocytes are among the most important inhibitors of carcinogenesis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tregs can suppress the function of immune effector cells, including Th17 cells, through a variety of mechanisms, and are key factors in tumor immune escape. A loss of balance between Th17 cells and Tregs is thought to be the primary mechanism of this escape (14,15). Previous studies have shown that the proportion of Tregs in the peripheral blood is significantly increased in patients with malignant tumors (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%